Androgen Receptor Is Dispensable for X-Zone Regression in the Female Adrenal but Regulates Post-Partum Corticosterone Levels and Protects Cortex Integrity - Gannon, Anne-Louise; O’Hara, Laura; Mason, Ian J.; Jørgensen, Anne; Frederiksen, Hanne; Curley, Michael; Milne, Laura; Smith, Sarah; Mitchell, Rod T.; Smith, Lee B. (Frontiers in Endocrinology, 2021)
Adrenal androgens are fundamental mediators of ovarian folliculogenesis, embryonic implantation and breast development. Although adrenal androgen function in target tissues are well characterised, there is little research covering the role of androgen-signalling within the adrenal itself. Adrenal glands express AR which is essential for the regression of the X-zone in male mice. Female mice also undergo X-zone regression during their first pregnancy, however whether this is also controlled by AR signalling is unknown. To understand the role of the androgen receptor (AR) in the female adrenal, we utilised a Cyp11a1-Cre to specifically ablate AR from the mouse adrenal cortex. Results show that AR-signalling is dispensable for adrenal gland development in females, and for X-zone regression during pregnancy, but is required to supress elevation of corticosterone levels post-partum. Additionally, following disruption to adrenal AR, aberrant spindle cell development is observed in young adult females. These results demonstrate sexually dimorphic regulation of the adrenal X-zone by AR and point to dysfunctional adrenal androgen signalling as a possible mechanism in the early development of adrenal spindle cell hyperplasia.